MANAGEMENT STRATEGY OF ISLAMIC EDUCATIONAL INSTITUTIONS IN THE FACE OF GLOBALIZATION IN MTsN 10 BOYOLALI - Agus Purnomo; Hery Setiyatna (Program Studi Manajemen Pendidikan Islam, 2026)
The management strategy of Islamic educational institutions in facing globalization is able to produce a strong generation of Muslims, mastering science and technology, and having noble morals. To achieve this goal, Islamic education must be managed optimally through Islamic Educational Institutions. This paper attempts to examine the success factors of Islamic Educational Institutions. This study focuses on the management of Islamic Educational Institutions to face the challenges of globalization. This research is a qualitative literature study interview. The results of the literature study indicate that the management of quality Islamic Educational Institutions requires management models such as the management model of Entrepreneurship-based Islamic Educational Institutions, the management model of community/society-based Islamic Educational Institutions, and the management model of mosque-based Islamic Educational Institutions. In addition, quality Islamic Educational Institutions require both general and specific management strategies. Specifically known as strategic management. The management of Islamic Educational Institutions is carried out using management functions, namely: planning, organizing, mobilizing, monitoring and evaluation, often referred to as POACE